Sustainable waste management: observing the economic and environmental aspects in solid waste recycling by the poor migrants in Indonesia / Eusoff Yendo Afgani ... [et al.] - Afgani, Eusoff Yendo; Kamaruddin, Norhaya; Mohd. Ali, Hishamuddin; Mar Iman, Abdul Hamid (2008)
This paper addresses the role of recycling activities among the migrant urban poor based on a recent study conducted in Jakarta, Indonesia. The study involved a survey among solid waste scavengers and field observations particularly on the collection and disposal of recyclable solid waste and the resulting revenue generated from the activities. The study revealed that the average per capita monthly amount of collected solid waste was 60-270 kg of paper, 30-95 kg of metal, 120-180 kg of plastics, 150-200 kg of tyre tube, and 30-90 kg of glass bottles. The study also revealed that the recycling activities could have resulted in the reduction of 390-800 kg of solid waste that would otherwise need to be transported to and disposed of at the designated dump sites. The net benefit to the Government as a result of the participation from the urban migrant poor in solid waste recycling activities was estimated to be US$ 7,128,666 to US$ 14,166,666 monthly.